Ratio of fat-free mass to fat mass is associated with physical performance in patients with type 2 diabetes mellitus - Sung, Jui-Hsiang; Ko, Fu-Shun; Wu, Tsung-Hui; Tsai, Shiow-Chwen; Hwu, Chii-Min; Su, Guan-Yu (Frontiers in Endocrinology, 2025)
BackgroundThe ratio of fat-free mass (FFM) to fat mass (FM) is a key indicator of body composition. Evidence suggests that the FFM/FM ratio is more reliable than body mass index in predicting functional outcomes in older adults with prefrailty. Individuals with type 2 diabetes mellitus (T2DM) exhibit higher FM and faster lean mass loss than do those without T2DM. In this study, we determined whether the FFM/FM ratio can predict functional outcomes in patients with T2DM.MethodsThis study enrolled 166 men and 173 women aged ≥50 years who received a T2DM diagnosis at least 1 year before the initiation of this study. Participants were recruited from Taipei Veterans General Hospital, Taiwan, between April 2019 and December 2023. Based on the FFM/FM ratio, patients were stratified into three groups: high, middle, and low tertiles. Body composition was assessed using InBody 3.0. Physical performance was evaluated through the Short Physical Performance Battery and gait speed measurement. The FFM/FM ratio was calculated using established formulas. Stepwise multiple regression was performed to identify the predictors of the FFM/FM ratio in patients stratified by sex.ResultsIn both sexes, individuals in the high-tertile group exhibited superior physical performance than did the other groups, as indicated by higher Short Physical Performance Battery scores (P < 0.001 for both sexes), better performance in the 30-second chair stand test (P < 0.001), faster gait speed in the 6-m walk (P <0.001), and shorter completion time in the timed up and go test (P <0.001). In men, waist circumference, upper arm circumference, age, logarithmic transformation of alanine transaminase level, and uric acid level emerged as independent predictors of the FFM/FM ratio. In women, waist circumference, upper arm circumference, age, and uric acid level emerged as independent predictors; notably, logarithmic transformation of alanine transaminase level was not included in the regression model.ConclusionThe present study revealed that a decreased FFM/FM ratio is associated with suboptimal physical performance in patients with T2DM, and this ratio may provide meaningful clinical benefits in targeting body composition in this population.